A new species of the South American genus Arthurella Albuquerque (Diptera: Muscidae), with a key to species and new records - Patitucci, Luciano Damián; Mariluis, Juan Carlos; Aballay, Fernando Hernán (Zootaxa, 2011)
The monotypic genus Arthurella Albuquerque, 1954 was originally described for A. nudiseta with a distribution restricted to Chile and Argentina. We add one new species, Arthurella choelensis sp. nov., from the central part of Argentina, and new distribution records for A. nudiseta. Biological and distributional information is given for both species. An identification key to the species of the genus is provided.